Supply Chain Strategy Development for Business and Technological Institution in Developing Start-up Based on Creative Economy - Ali Hapzi; Andi Desfiandi; M. Ariza Eka Yusendra; Niken Paramitasari (International Journal of Supply Chain Management, 2019)
This study aims to find a model based on the supply chain strategy, for the development of business incubator institutions and technology and operational work methods in the form of business incubation, case study at IIB Darmajaya. The method used to conduct this study is a combination of qualitative approaches such as in-depth interviews, participant observation, case studies, and grounded theory for the supply chain strategy. The activities are divided into several stages, starting from business, and technology incubator modeling, business competition creation, development of business incubation stages for students, to monitoring and evaluating business activities carried out by entrepreneurial students. The results of the study were a comprehensive and collaborative business and technology incubator in supply chain working model with various campus entrepreneurial stakeholders and six successful stages of entrepreneurial incubation.